2019
DOI: 10.1016/j.jcrysgro.2018.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of nitrogen-phosphorus hybrid passivated gate oxide film on N-type 4H-SiC epilayer

Abstract: A novel nitrogen-phosphorus (N&P) hybrid passivation technique by NO-containing dry oxidation of phosphorus-implanted 4H-SiC epilayer has been proposed to grow high-property gate oxide film. For demonstration and contrast, n-type 4H-SiC MOS capacitors with N&P hybrid and only N passivation have been fabricated and tested. The results from Secondary Ion Mass Spectroscopy (SIMS) reveal that about 60 % of the implanted phosphorus atoms remain in the SiO 2 film after sacrificial oxidation of the implantation layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In the case of phosphorus, secondary ion mass spectrometry (SIMS) has suggested the full conversion of SiO 2 into PSG, with a uniform concentration of P through the layer. 20,30 X-ray photoelectron spectroscopy (XPS) measurements have indicated a uniform atomic fraction for P of 5% within the PSG layer. 22 Using transmission electron microscopy (TEM), Fiorenza et al 31 reported a similar finding of P "almost homogeneously distributed within a) the insulating layer" as measured with energy dispersive X-ray spectroscopy (TEM-EDS).…”
mentioning
confidence: 99%
“…In the case of phosphorus, secondary ion mass spectrometry (SIMS) has suggested the full conversion of SiO 2 into PSG, with a uniform concentration of P through the layer. 20,30 X-ray photoelectron spectroscopy (XPS) measurements have indicated a uniform atomic fraction for P of 5% within the PSG layer. 22 Using transmission electron microscopy (TEM), Fiorenza et al 31 reported a similar finding of P "almost homogeneously distributed within a) the insulating layer" as measured with energy dispersive X-ray spectroscopy (TEM-EDS).…”
mentioning
confidence: 99%